2016
DOI: 10.1111/1752-1688.12413
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Fine‐Resolution Hydrological Modeling Using Parameter Regionalization in the Missouri River Basin

Abstract: This study simulated crop and water yields in the Missouri River Basin (MRB; 1,371,000 km2), one of the largest river basins in the United States, using the Soil and Water Assessment Tool (SWAT) at a fine resolution of 12‐digit Hydrological Unit Codes (HUCs) using the regionalization calibration approach. Very few studies have simulated the entire MRB, and those that have developed were at a coarser resolution of 8‐digit HUCs and were minimally calibrated. The MRB was first divided into three subbasins and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 84 publications
1
27
0
Order By: Relevance
“…Overall, the performance scores of model calibration and validation shown in Figure can be considered satisfactory according to the evaluation recommendations by Moriasi et al (), Moriasi, Gitau, Pai, and Daggupati (), and Moriasi et al (). The model performance shown here is comparable to various other large‐scale SWAT applications as well (e.g., Abbaspour et al, ; Daggupati et al, ; Daggupati et al, ).…”
Section: Resultssupporting
confidence: 82%
“…Overall, the performance scores of model calibration and validation shown in Figure can be considered satisfactory according to the evaluation recommendations by Moriasi et al (), Moriasi, Gitau, Pai, and Daggupati (), and Moriasi et al (). The model performance shown here is comparable to various other large‐scale SWAT applications as well (e.g., Abbaspour et al, ; Daggupati et al, ; Daggupati et al, ).…”
Section: Resultssupporting
confidence: 82%
“…Daggupati et al [15] reported that observed and simulated water yields in the head watersheds and those in the validation locations were in close agreement for naturalized stream systems within the MRB.…”
Section: Introductionmentioning
confidence: 74%
“…Daggupati et al [15] followed a protocol similar to Pagliero et al [14] and simulated water and crop yields in one of the few reported model simulation investigations of the entire Missouri River Basins (MRB) located in the north central portion of the U.S. After obtaining satisfactory results from flow calibration at the head watersheds in their delineated project, they used a regionalization calibration approach to transfer the calibration parameter set from each head watershed was to the subwatersheds within eleven MRB regions. Daggupati et al [15] reported that observed and simulated water yields in the head watersheds and those in the validation locations were in close agreement for naturalized stream systems within the MRB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall goal of this study is to demonstrate that better representation of PET/AET plays a key role in creating a robust hydrologic model by increasing the accuracy of both water and energy balance. SWAT (Arnold et al, ; Neitsch et al, ) is used in this study for hydrologic modeling because of its wide‐ranging applications in different geographic and hydroclimatic settings around the world for simulating water availability, sediment/nutrient transport, and crop yield (e.g., Abbaspour et al, ; Daggupati et al, ; A. Rajib & Merwade, ; Schuol et al, ; Zang et al, ). Four modeling experiments are performed (Table ) involving three U.S. watersheds: Upper Wabash and Cedar Creek in Indiana and Saline River in Arkansas (Figure ).Upper Wabash watershed (18,500 km 2 ) is the largest among the three test beds with several streamflow gauge stations.…”
Section: Methodsmentioning
confidence: 99%